Preliminary analysis of association of m7G methyltransferase 1 with pan-cancer prognosis and immune infiltration - CHENG Wenli; FU Jiaqi; ZHU Chenyu; ZHANG Xinyu; TAN Luyi; ZHANG Wenjuan (Guangxi Yike Daxue xuebao)
Objective To investigate the expression of RNA m7G methyltransferase 1 (METTL1) in various types of tumors and its association with prognosis and immune infiltration, in order to provide a new reference for the screening of cancer biomarkers and their mechanisms of occurrence and development. Methods The Cancer Genome Atlas (TCGA) was used to analyze the mRNA expression profile of METTL1 in 33 tumors and the differences in METTL1 expression between the tumor group and the normal control group. Cox regression model and Kaplan-Meier were used to analyze the correlation between METTL1 expression and the prognosis of cancer patients. The association between METTL1 expression and immune infiltration in liver hepatocellular carcinoma (LIHC) was analyzed, and the mRNA expression levels of METTL1 and immune checkpoint in normal hepatocytes and LIHC cells were preliminatively verified by fluorescence quantitative PCR. Results The expression level of METTL1 was different between cancer tissues and adjacent tissues, and it was highly expressed in most cancer tissues. High expression of METTL1 significantly shortened the median survival time of patients with low grade glioma (LGG), LIHC and mesothelioma (MESO). The expression level of METTL1 in LIHC was positively correlated with the levels of multiple inflammatory cells. And the expression level of METTL1 was positively correlated with the expression of immune checkpoints LAG3 and PDCD1 (P＜0.001), which was consistent with the mRNA expression level in cultured LIHC cells in vitro. Conclusion METTL1 significantly promotes the occurrence and progression of most tumors, negatively regulates the prognosis survival rate of LGG, LIHC and MESO patients, and is positively correlated with immune infiltration. METTL1 is expected to be a cancer biomarker based on LAG3 and PDCD1 immunotherapy.